Studi Penggunaan Game Online Free Fire Pada Emosi Siswa Kelas 5 Di SDN 2 Braja Harjosari - Ade Surya Erofiana; Gunawan Santoso; Suryadi Nomi (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The background of this thesis writing is the excessive number of children's behavior in playing online games, especially free fire online games where many children who live in the village of Braja Harjosari are very excessive in their behavior to play online free fire games, even many emotional behaviors appear. when they are playing with their friends. On the basis of this, the researcher was moved to examine how the behavior of using online free fire games on the emotions of 5th grade students of SDN 2 Braja Harjosari. The method used in this research is a qualitative case study method. The results showed that the level of excessive use in playing online games, especially free fire online games at SDN 2 Braja Harjosari had a negative impact on children's emotional intelligence, where from the use of online free fire games it was proven that children had emotional levels that tended to be uncontrollable, game users. Online free fire tends to express emotions in various ways including hitting, kicking, impatience, saying harshly, slamming cellphones and so on. Thus it can be concluded that excessive use in online free fire games can affect students' emotions to become uncontrollable. The results of this study are expected to be useful for related parties such as parents, teachers, schools, students, and further researchers.